1997
DOI: 10.1097/00007632-199712150-00014
|View full text |Cite
|
Sign up to set email alerts
|

A Population-Based, Randomized Clinical Trial on Back Pain Management

Abstract: Close association of occupational intervention with clinical care is of primary importance in impeding progression toward chronicity of low back pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
232
6
14

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 416 publications
(261 citation statements)
references
References 12 publications
9
232
6
14
Order By: Relevance
“…The absence of this information and the need for effective RTW measures has prompted the development of a new ''coordinated and tailored work rehabilitation'' (CTWR) approach, based on a Canadian multidisciplinary work rehabilitation program (i.e., the Sherbrooke model by Loisel et al) [7,[15][16][17]. Loisel et al [16] found that the combination of an occupational intervention and a clinical rehabilitation intervention was effective on disability and RTW. The Sherbrooke model has inspired other similar studies outside Canada, like the study on multidisciplinary rehabilitation for subacute low back pain in The Netherlands [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…The absence of this information and the need for effective RTW measures has prompted the development of a new ''coordinated and tailored work rehabilitation'' (CTWR) approach, based on a Canadian multidisciplinary work rehabilitation program (i.e., the Sherbrooke model by Loisel et al) [7,[15][16][17]. Loisel et al [16] found that the combination of an occupational intervention and a clinical rehabilitation intervention was effective on disability and RTW. The Sherbrooke model has inspired other similar studies outside Canada, like the study on multidisciplinary rehabilitation for subacute low back pain in The Netherlands [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have shown how interventions at the workplace contribute to return to the original job [1][2][3][4]. These interventions are appropriate for many workers, and contribute to the fact that most people on sick leave resume work within a limited amount of time.…”
Section: Introductionmentioning
confidence: 99%
“…Daltroy et al 1997;Loisel et al 1997), there are few in office environments (for a review see Karsh et al 2001;NRC 2001). The small number of office intervention studies has focused on either ergonomic training (Brisson et al 1999;Hinman et al 1997;Kamwendo and Linton 1991), alternate input devices Tittiranonda et al 1999), or a broader set of office environment changes (Aaras et al 1999(Aaras et al , 2001Nelson and Silverstein 1998;Rudakewych et al 2001).…”
Section: Introductionmentioning
confidence: 99%